Does arsenic increase the risk of neural tube defects among a highly exposed population? A new case–control study in Bangladesh. Issue 2 (30th January 2017) - Mazumdar, Maitreyi
Abstract : Background: Neural tube defects are debilitating birth defects that occur when the developing neural plate fails to close in early gestation. Arsenic induces neural tube defects in animal models, but whether environmental arsenic exposure increases risk of neural tube defects in humans is unknown. Methods: We describe a new case–control study in Bangladesh, a country currently experiencing an epidemic of arsenic poisoning through contaminated drinking water. We plan to understand how arsenic influences risk of neural tube defects in humans through mechanisms that include disruption of maternal glucose and folate metabolism, as well as epigenetic effects. We also investigate whether sweat chloride concentration, a potential new biomarker for arsenic toxicity, can be used to identify women at higher risk for having a child affected by neural tube defect. We will collect dural tissue from cases, obtained at the time of surgical closure of the defect, and believe investigation of these samples will provide insight into the epigenetic mechanisms by which prenatal arsenic exposure affects the developing nervous system. Conclusion: These studies explore mechanisms by which arsenic may increase risk of neural tube defects in humans and use a unique population with high arsenic exposure to test hypotheses. If successful, these studies may assist countries with high arsenic exposure such as Bangladesh to identify populations at high risk of neural tube defects, as well as direct development of novel screening strategies for maternal risk.Birth Defects Research 109:92–98, 2017.© 2016 The Authors Birth Defects Research Published by Wiley Periodicals, Inc.